Diseases attributable to asbestos exposure: Years of potential life lost, United States, 1999–2010. Issue 1 (20th September 2013) - Bang, Ki Moon; Mazurek, Jacek M.; Wood, John M.; Hendricks, Scott A.
Abstract Background Although asbestos use has been restricted in recent decades, asbestos‐associated deaths continue to occur in the United States. Objectives We evaluated premature mortality and loss of potentially productive years of life attributable to asbestos‐associated diseases. Methods Using 1999–2010 National Center for Health Statistics mortality data, we identified decedents aged ≥25 years whose death certificate listed asbestosis and malignant mesothelioma as the underlying cause of death. We computed years of potential life lost to life expectancy (YPLL) and to age 65 (YPLL65). Results During 1999–2010, a total of 427, 005 YPLL and 55, 184 YPLL65 were attributed to asbestosis (56, 907 YPLL and 2, 167 YPLL65), malignant mesothelioma (370, 098 YPPL and 53, 017 YPLL65). Overall and disease‐specific asbestos‐attributable total YPLL and YPLL65 and median YPLL and YPLL65 per decedent did not change significantly from 1999 to 2010. Conclusions The continuing occurrence of asbestos‐associated diseases and their substantial premature mortality burden underscore the need for maintaining prevention efforts and for ongoing surveillance to monitor temporal trends in these diseases. Am. J. Ind. Med. 57:38–48, 2014. © 2013 Wiley Periodicals, Inc.